Yeha, Äthiopien: Die Klosterkirche Debre Mariam - Krizwon, Annika (e-Forschungsberichte des DAI, 2023)
Within the Ethiopian-German research project in Yeha the church “Debre Mariam” of the monastery “Enda Abuna Afse” was investigated as a master’s thesis for the programme “Heritage Conservation” at the Technical University of Berlin. The main focus of this study was to produce a ground plan based on 3D-Laserscanning-technique as well as an accurate specification of the entire structure.